1984
DOI: 10.1029/rg022i002p00195
|View full text |Cite
|
Sign up to set email alerts
|

An overview of passive microwave snow research and results

Abstract: The current state of knowledge of the microwave properties of snow is discussed. Theory behind the microwave emission from snow is reviewed, as are the physical processes of snowpack metamorphism. Field, aircraft, and satellite passive microwave data have been acquired and analyzed for more than 10 years. Results have repeatedly demonstrated the feasibility of employing multifrequency passive microwave data to study snow‐covered area, snow depth, and internal snowpack properties. Radiation emanating from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(68 citation statements)
references
References 23 publications
1
67
0
Order By: Relevance
“…The deeper the snowpack, the more crystals are available to scatter microwave energy away from the sensor. Hence, microwave brightness temperatures are generally colder, or lower, for deep snowpacks than they are for shallow snowpacks (Foster et al, 1984). Drawbacks of the microwave approach include poor resolution and difficulty in interpreting the effects of snow structure on microwave response and in understanding microwave emission and interaction with other media (Hall et al, 1985(Hall et al, , 1991.…”
Section: Introductionmentioning
confidence: 99%
“…The deeper the snowpack, the more crystals are available to scatter microwave energy away from the sensor. Hence, microwave brightness temperatures are generally colder, or lower, for deep snowpacks than they are for shallow snowpacks (Foster et al, 1984). Drawbacks of the microwave approach include poor resolution and difficulty in interpreting the effects of snow structure on microwave response and in understanding microwave emission and interaction with other media (Hall et al, 1985(Hall et al, , 1991.…”
Section: Introductionmentioning
confidence: 99%
“…For example, assessments of snow extent, derived from the National Oceanic and Atmospheric Administration (NOAA) visible and near-infrared imagery under cloud-free conditions, have been available for 25 yr (e.g., Kukla and Kukla 1974;Matson et al 1986;Robinson et al 1993). Likewise, passive microwave sensors have proven useful for monitoring snow extent and water equivalent, through cloud cover and darkness (Rango et al 1979;Kunzi et al 1982;Foster et al 1984;Goodison et al 1986;Chang et al 1987), although there are problems related to the detection of thin dry snow (producing insufficient signal to differentiate it from the underlying surface), and shallow wet snow (having an emittance similar to bare, wet ground).…”
Section: B Influences Of High Latitudes On Global Climatementioning
confidence: 99%
“…Passive microwave sensors which sense the emitted radiation can provide information regarding the internal characteristics of snow and ice (Chang and others, 1976). Previous studies have shown that there is an inverse relationship between snow depth and microwave TB as measured by passive microwave sensors at specified wavelengths in dry snow (Foster and others, 1984). The 37 GHz (0.81 cm wavelength) sensor of the Scanning Multichannel Microwave Radiometer (SMMR) on board the Nimbus-7 satellite has been shown to be particularly useful for analyzing internal properties of snow-packs especially when the horizontally polarized data are used (Hall and others, 1984).…”
Section: Theoretical Basis For Microwave Observa-tionsmentioning
confidence: 99%